Bactericidal action of ofloxacin, sulbactam-ampicillin, rifampin, and isoniazid on logarithmic- and stationary-phase cultures of Mycobacterium tuberculosis. - Herbert, D (1996)
The bactericidal actions of ofloxacin and sulbactam-ampicillin, alone and in combination with rifampin and isoniazid, on exponential-phase and stationary-phase cultures of a drug-susceptible isolate of Mycobacterium tuberculosis were studied in vitro. In exponential-phase cultures, all drugs were bactericidal, with the higher concentrations of ofloxacin (5 micrograms/ml) and sulbactam-ampicillin (15 micrograms of ampicillin per ml) being as bactericidal as 1 microgram of isoniazid per ml or 1 microgram of rifampin per ml. In two-drug combinations, both drugs increased the levels of activity of isoniazid and rifampin and were almost as bactericidal as isoniazid-rifampin; they also appeared to increase the level of activity of isoniazid-rifampin in three-drug combinations. In contrast, ofloxacin and sulbactam-ampicillin had little bactericidal activity against stationary-phase cultures and were less active than isoniazid or rifampin alone. Furthermore, in two-drug or three-drug combinations, they did not increase the level of activity of isoniazid, rifampin, or isoniazid-rifampin. These findings suggest that ofloxacin and sulbactam-ampicillin are likely to be most useful in the early stages of treatment and in preventing the emergence of resistance to other drugs but are unlikely to be effective as sterilizing drugs helping to kill persisting lesional bacilli.